Accounting for Hybridized Activities in University Students’ Video-Mediated Breakout Room Interactions - Elina Helmiina Nuutinen (Social Interaction)
Using video recordings collected from an online language course, this study examines activities that university students engage in simultaneously while doing groupwork in breakout rooms on zoom. As a method, this study employs multimodal conversation analysis to shed light on the students’ verbal accounts (i.e., verbalizations of the activity) for their hybridized activities, in particular how their verbal accounts make visible varying levels of moral entitlement, and how their peers react to these accounts. The findings show that the students produce accounts at various points in sequences (before the activity, during the activity, or after the activity has ended). Whilst contingent on the situation at hand, the nature of the hybridized activity, as well as the level of entitlement in the account produced affected whether the responses prompted were aligning/affiliating or disaligning/disaffiliating (see Steensig, 2019) in relation to the accounts. Overall, this study contributes to the existing literature on “fractured ecologies” in video-mediated interactions (Luff et al., 2003), while also drawing implications to the lack of monitorability and to what seems to be an increased tolerance towards multitasking in video-mediated educational interactions.